2021
DOI: 10.1039/d0sc02342f
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of hydrated AcIII cation: the role of superatom states in actinium-water bonding

Abstract: The stable 9-coordinated complex adopts a closed-shell 18-electron configuration of a 1S21P61D10 jellium state, while potential 10-coordinated complexes need to overcome an energy barrier (>0.10 eV) caused by hydrogen bonding to convert to 9-coordination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 93 publications
2
24
0
Order By: Relevance
“…For lanthanides with smaller ionic radii, eight coordination sites (or the size of the inner cavity) may be suitable, but for actinides with larger ionic radii, a higher coordination number is required. For example, only nine-coordinated [An III (DOTA)­(H 2 O)] − (An = Pu, Am) were characterized by X-ray crystallography, whereas [An III (DOTA)] − complexes were not. , Further research found that changes in the ninth coordination species can not only directly affect the spectroscopic, magnetic, and electronic structure properties of the complex but also change the oxidation state of the central Ln/An atom. Therefore, a systematic study on the interaction between the [An III (DOTA)] − fragment and different axial ligands could provide a detailed characterization of actinide chelation chemistry in a fruitful and convenient way.…”
mentioning
confidence: 99%
“…For lanthanides with smaller ionic radii, eight coordination sites (or the size of the inner cavity) may be suitable, but for actinides with larger ionic radii, a higher coordination number is required. For example, only nine-coordinated [An III (DOTA)­(H 2 O)] − (An = Pu, Am) were characterized by X-ray crystallography, whereas [An III (DOTA)] − complexes were not. , Further research found that changes in the ninth coordination species can not only directly affect the spectroscopic, magnetic, and electronic structure properties of the complex but also change the oxidation state of the central Ln/An atom. Therefore, a systematic study on the interaction between the [An III (DOTA)] − fragment and different axial ligands could provide a detailed characterization of actinide chelation chemistry in a fruitful and convenient way.…”
mentioning
confidence: 99%
“…When 225 Ac-DOTA-benzene-p-SCN was injected intratumorally in nude mice bearing HEP-G2 tumors, a very rapid clearance of radioactivity from the tumor was observed ( Figure 5 b); and almost 10-fold higher uptake in liver and spleen was seen with regard to the 225 Ac-rHDL biodistribution pattern ( Figure 5 b). These findings suggest that although the DOTA chelating agent is highly stable for positive trivalent radiometals [ 12 , 24 , 25 ], 225 Ac-DOTA-benzene-p-SCN does not remain in the tumor, because the recoil energy of the 225 Ac daughters (1000 times greater than the binding energy of any chemical compound) is possibly causing the breaking of chemical bonds, with the consequent retention of 225 Ac 3+ and its progeny in the liver as ionic forms [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…All complexes were chosen to have 9‐coordinate geometries with a tricapped trigonal prismatic (TTP) arrangement of donor atoms around the central Ac 3+ ion. This choice of coordination number (CN) 9 was motivated by DFT studies of the Ac 3+ ion with 4–11 water molecules where [Ac(H 2 O) 9 ] 3+ was shown to be the most stable, both, in the gas phase and the aqueous phase (COSMO model) 26 . Keeping the coordination number fixed also provides internal consistency thanks to the similar steric crowding around the Ac metal center.…”
Section: Resultsmentioning
confidence: 99%
“…(The longest‐lived isotope, 227 Ac, has a half‐life of about 21.7 years.) Thus, computational methods are applied to actinium chemistry and to improve the chelate design 13,22–26 . Other theoretical studies investigated the maximum possible coordination number of Ac 3+ and found that up to 18 helium atoms can be accommodated giving a stable complex [AcHe 18 ] 3+ in the gas phase 27,28 …”
Section: Introductionmentioning
confidence: 99%